Pax Syriana: Elite Politics in Postwar Lebanon By Rola el-Husseini (Syracuse: Syracuse University Press, 2012. 319 pages.) (American Journal of Islam and Society, 2014)
There has rarely been a dull period in Lebanon’s post-Ottoman political history.Its central geographic, if not political, position within the Arab region,along with its penetrable political system, has made the country vulnerable toregional and international pressures. These pressures have manifested themselvesin both spectacular (e.g., the civil war and Israeli occupation) and moresubtle ways (e.g., the sustained brain drain and continued socioeconomic deprivationof rural communities). Despite these changes, however, the country’spolitical system has remained resilient and the sectarian power-sharing system104 The American Journal of Islamic Social Sciences 31:2forming the core of national politics and distribution of (formal and informal)political power has changed only in style, not substance.Rola el-Husseini’s inquiry into the country’s political elite background,structure, politics, recruitment patterns, and discourses is layered against theresiliency of its confessional system. Her core concern is to trace theLebanese elite’s interactions and their major structural determinants. As such,the inquiry has to ask how the period of Syrian control – Pax Syriana – creatednew possibilities and limitations for elite politics in Lebanon. Thus,while the text is rich in historical analysis and sound in its treatment ofLebanon’s postcolonial politics, the main period of focus is on 1991 to 2005,when Syrian influence was at its peak. As one would expect, Syria’s influenceon elite recruitment and this class’ politics and discourses was profound duringthis period ...